Multiple, thin-walled cysts are one of the HRCT features of airspace enlargement with fibrosis. Issue 5 (May 2015) - Watanabe, Yasutaka; Kawabata, Yoshinori; Kanauchi, Tetsu; Hoshi, Eishin; Kurashima, Kazuyoshi; Koyama, Shinichiro; Colby, Thomas V.
Highlights: High resolution computed tomography (HRCT) findings of airspace enlargement with fibrosis (AEF), recently identified as a smoking related change. Investigation was in 35 smokers. They underwent lobectomy for lung cancer with pathological confirmation of AEF. Multiple, thin-walled cysts are one of the HRCT features of AEF. Abstract: Purpose: Airspace enlargement with fibrosis (AEF) has been identified pathologically as a smoking related change. We sought to identify the HRCT findings of AEF and search for distinguishing features from honeycombing. Materials and methods: 50 patients (47 males; mean age 69) were evaluated. All had undergone lobectomy for lung cancer and had confirmed AEF and/or usual interstitial pneumonia (UIP) by pathological evaluation. HRCT findings were first evaluated preresection for resected lobes, and then correlated with the subsequent pathological findings in the resection specimens. Three groups were devised: one with AEF alone to determine the HRCT findings of AEF, a second with AEF and UIP and third with UIP alone. HRCT features of AEF and honeycombing were compared. Results: There were 11 patients (10 male; mean age 69) with AEF alone, 24 patients (22 male; mean age 69) with AEF and UIP, and 15 patients (15 male; mean age 68) with UIP alone. The HRCT on the AEF alone showed subpleural (but not abutting the pleura) multiple thin-walled cysts (MTWCs) in 7 and reticular opacities in 3. The HRCT in AEF and UIP showed MTWCs in 10, reticular opacities in 17; and honeycombing in 5. Among these 35 patients with the pathological finding of AEF (with or without UIP), 17 showed MTWCs. The maximum cyst wall thickness of MTWCs (mean 0.81 mm) was significantly thinner than that of honeycombing (mean 1.56 mm). MTWCs did not locate in lung base and was distant from the pleura. HRCT findings correlated with gross findings on both cysts and honeycombing. No MTWCs were seen in the 15 patients with UIP, 8 of 15 had honeycombing on CT. Conclusions: We confirmed that HRCT features of AEF were MTWCs and/or reticular opacities. MTWCs might be distinguished from those of honeycomb change. While we prefer the term MTWCs, these sorts of changes have probably been confused with/interpreted as honeycombing and/or empysema in the past.